2021
DOI: 10.1007/s10311-020-01171-x
|View full text |Cite
|
Sign up to set email alerts
|

Metal oxide electron transport materials for perovskite solar cells: a review

Abstract: Solar electricity is an unlimited source of sustainable fuels, yet the efficiency of solar cells is limited. The efficiency of perovskite solar cells improved from 3.9% to reach 25.5% in just a few years. Perovskite solar cells are actually viewed as promising by comparison with dye-sensitized solar cells, organic solar cells, and the traditional solar cells made of silicon, GaAs, copper indium gallium selenide (CIGS), and CdTe. Here, we review bare and doped metal oxide electron transport layers in the perovs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(94 citation statements)
references
References 150 publications
2
86
0
Order By: Relevance
“…Planar structure uses multiple stacked thin layers, such as the photoactive perovskite layer is sandwiched between the HTL and ETL. As the detail investigations of basic principles, fabrication protocols, materials and methods of PSCs are beyond the scope of current study, for more details we encourage readers to refer to recently published reviews [ 59 , 60 , 61 ].…”
Section: Structure Of Pscsmentioning
confidence: 99%
“…Planar structure uses multiple stacked thin layers, such as the photoactive perovskite layer is sandwiched between the HTL and ETL. As the detail investigations of basic principles, fabrication protocols, materials and methods of PSCs are beyond the scope of current study, for more details we encourage readers to refer to recently published reviews [ 59 , 60 , 61 ].…”
Section: Structure Of Pscsmentioning
confidence: 99%
“…Group B is a small inorganic cation (Cu 2+ , Sn 2+ , Pb 2+ ) and X3 is an ion that is capable of bonding A and B such as Cl -, Brand Ias shown in Fig. 4 [3,14,20,21].…”
Section: Perovskitementioning
confidence: 99%
“…Regardless of the PSC high efficiency, there is a lack of reasons for PSC degradation and instability which is an obstacle for commercialization in our life. Therefore, there is a need for more information about the cell for further improvement in performance and stability [14] and must take the minimum recombination and maximum separation of charges considerable for higher performance [15]. Consequently, based on previous studies, this review introduces various PSC structures and the techniques of this new technology, makes a comparison between them to get the points of shortage to be able to optimize this technology and determine the most promising and reliable materials, structures that help to get the best performance in the future work.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many experimental reports have indicated that the NFRHT can exceed the blackbody limit for a plane-plane configuration [33][34][35][36][37][38]. Therefore, NFRHT is of great significance in a variety of engineering applications, such as energy management [17,[39][40][41][42], sensing, and micro/nano-electromechanical systems (M/NEMS) [43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%